Altered pressure pain thresholds and increased wind-up in adult patients with chronic back pain with a history of childhood maltreatment: a quantitative sensory testing study - Tesarz, Jonas; Eich, Wolfgang; Treede, Rolf-Detlef; Gerhardt, Andreas (Pain, 2016)
Childhood maltreatment (CM) has been associated with an increased risk of nonspecific chronic low back pain (nsCLBP). However, the mechanisms underlying this association are unclear. Therefore, this study considered whether distinct types of CM are accompanied by specific alterations in somatosensory function. A total of 176 subjects with nsCLBP and 27 pain-free controls (PCs) were included. The Childhood Trauma Questionnaire (CTQ) was used to categorize patients into 2 groups (abused/neglected vs nonabused/nonneglected) for 5 types of CM (emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect). The standardized quantitative sensory testing protocol of the “German Research Network on Neuropathic Pain” was performed to obtaincomprehensive profiles on somatosensory function, including detection and pain thresholds, pain sensitivity, and assessments of temporal summation (wind-up). Between 17.7% and 51.4% of subjects with nsCLBP reported CM, depending on the type of CM. Childhood Trauma Questionnaire subscores for emotional and sexual abuse were significantly higher in subjects with nsCLBP than in PCs. Compared with PCs, subjects with CM showed reduced pressure pain thresholds (PPTs), irrespective of the type of CM. Regarding distinct types of CM, subjects with nsCLBP with emotional abuse reported significantly higher wind-up than those without,and sexual abuse was accompanied by enhanced touch sensitivity. Our findings suggest that CM is nonspecifically associated with a decreased PPT in nsCLBP. Emotional abuse apparently leads to enhanced spinal pain summation, andsexual abuse leads to enhanced touch sensitivity. These results emphasize the importance of emotional abuse in nsCLBP and suggest that CM can induce long-term changes in adult somatosensory function.
Gesehen am 15.08.2019